Perekonomian Tradisi Kampung Pulo Dengan Candi Cangguang Sebagai Peninggalan Sejarah Di Garut Jawa Barat - Reni, Reni Suryani; Dauman; Ilhamsyah Lubis; Eliana; Arief Widyanto; Suko (Pamulang Law Review, 2025)
To find out whether there are legal regulations that are in accordance with legal norms and The traditional economy of Kampung Pulo, with Cangkuang Temple as a historical relic in Garut, West Java, illustrates the interaction between cultural heritage and local economic dynamics. Established in the 18th century, Kampung Pulo reflects a rich history, imbued with a blend of Hinduism and Islam, which has shaped the identity of the local community. Cangkuang Temple, as a historical site, serves not only as a spiritual symbol but also as a tourist attraction, contributing to the local economy. In this context, the economy of Kampung Pulo is inextricably linked to the rapidly growing tourism sector. Economic activities such as the sale of traditional food, handicrafts, and the provision of tourism services offer opportunities for the community to preserve traditions while increasing income. Sustainable tourism management in this area is expected to maintain cultural heritage and improve community welfare. However, challenges also arise, such as the threat of modernization that can erode local cultural values. Therefore, efforts to preserve traditions are crucial to ensure that the economy is not only financially profitable but also maintains the cultural identity of Kampung Pulo. This study aims to analyze the relationship between the traditional economy and historical heritage and explore strategies that can be implemented to maintain the economic and cultural sustainability of Kampung Pulo.